What happened to financially sustainable firms in the Corona crisis? - Thomas Günther; Werner Gleißner; Christian Walkshäusl (Sustainability Management Forum, 2020)
Purpose: Financial sustainability is underrepresented in both research on and the practice of sustainability management and reporting. In this article, we examine empirically how financially sustainable firms performed in the Corona crisis.Methods: We measure financial sustainability by four conditions: (1)~firm growth, (2)~the company's ability to survive, (3)~an acceptable overall level of earnings risk exposure, and (4)~an attractive earnings risk profile. We apply this measurement to investment portfolios of a~broad sample of firms from 15~European countries of the MSCI Europe using typical investment portfolio characteristics.Results: We find that financially sustainable firms outperform both the broad market and firms with low financial sustainability for the time span July 2019 to March 2020.Conclusion: An investment strategy that invests in financially sustainable firms seems to be better capable of overcoming economic breakdowns such as the Corona crisis. We find that the returns increase with each of the four conditions that are included in the investment strategy. This underlines that considering financial sustainability is interesting for financial management, corporate governance and management control.
Keywords: D81; M41; M48; 650; Sustainability; Financial sustainability; Risk management; Risk governance; Earnings risk; Rating